Automated eclipsing binary detection:applying the Gaia CU7 pipeline to Hipparcos. Issue 67 (17th July 2015) - Holl, B.; Mowlavi, N.; Lecoeur-Taïbi, I.; Barblan, F.; Rimoldini, L.; Eyer, L.; Süveges, M.; Guy, L.; Ordoñez-Blanco, D.; Ruiz, I.; Nienartowicz, K.
Abstract : We demonstrate the eclipsing binary detection performance of the Gaia variability analysis and processing pipeline using Hipparcos data. The automated pipeline classifies 1 067 (0.9%) of the 118 204 Hipparcos sources as eclipsing binary candidates. The detection rate amounts to 89% (732 sources) in a subset of 819 visually confirmed eclipsing binaries, with the period correctly identified for 80% of them, and double or half periods obtained in 6% of the cases.